Correlates of the victim–offender overlap based on daily conflict-Level data from digital diaries - Taylor, Bruce G. (Criminal justice and behavior, 2022)
This study addresses the dearth of research in the victim–offender (V-O) overlap literature regarding the context in which incident-level abuse occurs. With a national sample of 589 young adults (age 18–32), 9.2% reported 2,015 daily conflicts (73% involving abuse) through digital diaries over a 6-week period. Using individual conflicts as our unit of analysis, we estimated multilevel models to explore both the nature of the individual conflicts and the characteristics of the parties in the conflict. We explored what distinguishes routine nonabusive conflicts from conflicts that involve abuse. We also examined the predictors of abusive conflicts and the V-O overlap. The nature of the incidents and proximities of the parties to the conflict were associated with the presence of abuse in conflicts and the V-O overlap. How young adults manage conflicts played a role in whether the dispute escalated to include abusive behaviors, especially mutual abuse.